Whole-body diffusion-weighted magnetic resonance imaging versus FDG-PET/CT for initial lymphoma staging: systematic review on diagnostic test accuracy studies - Regacini, Rodrigo; Puchnick, Andrea; Shigueoka, David Carlos; Iared, Wagner; Lederman, Henrique Manoel (São Paulo Medical Journal, 2015)
CONTEXT AND OBJECTIVE: Positron emission tomography with [18]F-fluoro-2-deoxyglucose (FDG-PET/CT) has been advocated as the method of choice for lymphoma staging, since it enables whole-body analysis with high sensitivity for detection of affected areas and because it combines capacities for anatomical and functional assessment. With technological advances, magnetic resonance imaging (MRI) has emerged as an alternative to FDG-PET/CT. This systematic review with meta-analysis aimed to compare whole-body diffusion-weighted MRI (WB-MRI) with FDG-PET/CT for lymphoma staging. DESIGN AND SETTING: Systematic review on diagnostic test accuracy studies conducted at a public university. METHODS: The Medline, Scopus, Embase and Lilacs databases were searched for studies published up to September 2013 that compared WB-MRI and FDG-PET/CT for lymphoma staging. The reference lists of included studies were checked for any relevant additional citations. RESULTS: Six studies that evaluated the initial lymphoma staging in 116 patients were included. WB-MRI and FDG-PET/CT agreed in 90.5% of the cases (κ = 0.871; P < 0.0001). In most of the studies, when there was disagreement between the methods, WB-MRI overstaged in relation to FDG-PET/CT. The sensitivity of WB-MRI and FDG-PET/CT, in comparison with the clinical-radiological standard, ranged from 59 to 100% and from 63 to 100% respectively. CONCLUSION: WB-MRI is a highly sensitive method for initial lymphoma staging. It has excellent agreement with FDG-PET/CT and is a great alternative for managing lymphoma patients, without using ionizing radiation or an intravenous contrast agent.